Library and Information Science Literature in India: An Examination of Author-Assigned Keywords - Dapsi, Sonali; Ranjan Hatua, Sudip (Journal of Information and Knowledge, 2017)
The Study of articles published in Library and Information Science Journals in recent times suggests that author assigned keywords are largely uncontrolled. Despite knowledge of controlled vocabulary they mostly use NL phrases to represent the content. This paper examines keywords assigned by authors to papers published in Library and information Science journals in India in the last fifteen years (1998-2012).